The Artificial Intelligence as a One-Stop Point for Dealing with Online Human Trafficking Scams in Indonesia - Kusumowijoyo, Anindita; Marta, Anjani; Natali Boasrifa, Kimberly (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2023)
Human Trafficking is an organized transnational crime aimed at exploiting humans. As a result of the triple disruption phenomenon, human trafficking currently manifests with a new modus operandi, namely online scamming. This modus operandi is quite concerning as it exhibits recruitment patterns, victim characteristics, and perpetrator characteristics that are significantly different from conventional human trafficking. However, the government currently lacks a precise mechanism to address online scamming human trafficking. As a transnational crime, collective efforts based on technology need to be mobilized to eradicate and address online scamming human trafficking. Therefore, through a juridical-normative research method, this study aims to elucidate the challenges faced by the government in addressing online scamming human trafficking and to initiate ideas for a comprehensive human trafficking handling mechanism from upstream to downstream through prevention, intervention, and restoration of victims.